INTERACTIVE TEACHING METHODS IN TEACHING FOREIGN LANGUAGES METHODOLOGY: INTERACTIVE TEACHING METHODS IN TEACHING FOREIGN LANGUAGES METHODOLOGY - Almatova, Umida (Журнал иностранных языков и лингвистики, 2021)
The main purpose of the use of interactive methods in distance learning of foreign languages is to involve students in the process of active learning, to help them develop knowledge and research skills. Interactive methods are based on the active relationship between teacher and student, full understanding of each other. The ultimate goal of the introduction of interactive methods in the learning process is to organize the interaction of the teacher and the student in the classroom, regardless of the form of the lesson.